Thermal reactionomes reveal divergent responses to thermal extremes in warm and cool-climate ant species. (December 2016) - Stanton-Geddes, John; Nguyen, Andrew; Chick, Lacy; Vincent, James; Vangala, Mahesh; Dunn, Robert; Ellison, Aaron; Sanders, Nathan; Gotelli, Nicholas; Cahan, Sara
Abstract Background The distributions of species and their responses to climate change are in part determined by their thermal tolerances. However, little is known about how thermal tolerance evolves. To test whether evolutionary extension of thermal limits is accomplished through enhanced cellular stress response (enhanced response ), constitutively elevated expression of protective genes (genetic assimilation ) or a shift from damage resistance to passive mechanisms of thermal stability (tolerance ), we conducted an analysis of thereactionome : the reaction norm for all genes in an organism's transcriptome measured across an experimental gradient. We characterized thermal reactionomes of two common ant species in the eastern U.S, the northern cool-climateAphaenogaster picea and the southern warm-climateAphaenogaster carolinensis, across 12 temperatures that spanned their entire thermal breadth. Results We found that at least 2 % of all genes changed expression with temperature. The majority of upregulation was specific to exposure to low temperatures. The cool-adaptedA. picea induced expression of more genes in response to extreme temperatures than didA. carolinensis, consistent with theenhanced response hypothesis. In contrast, under high temperatures the warm-adaptedA. carolinensis downregulated many of the genes upregulated inA. picea, and required more extreme temperatures to induce down-regulation in gene expression, consistent with thetolerance hypothesis. We found no evidence for a trade-off between constitutive and inducible gene expression as predicted by thegenetic assimilation hypothesis . Conclusions These results suggest that increases in upper thermal limits may require an evolutionary shift in response mechanism away from damage repair toward tolerance and prevention.